Emergency Room Thoracotomy: A Multidisciplinary Approach for Emergency, Surgical, and Critical Care Teams - Alotaibi, Faisal Mesfer; Bader Ahmed Thamer Almsud,; Abdullah mohammed Abdullah Alameer,; Abdulmajeed Abdu Ahmed Maashi,; Talal Ali Alsharari,; Mohammed Fihat Alanazi,; Tariq Jumauan Dakheel Alsaedi,; Zainab Ali Jaffer Al Aseel,; Ayman Mohammed Saleh Al-Juaithen,; Khalid Mohammed Mohssen Khormi,; Mohammed Nasser Mohammed Dhamiri,; Talal Mohammed Alanazi,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Emergency room thoracotomy (ERT) is an aggressive resuscitative procedure performed in extreme, time-critical trauma scenarios. It aims to restore circulation and oxygen delivery by addressing life-threatening intrathoracic injuries such as hemorrhage, cardiac tamponade, and traumatic arrest. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This study reviews the multidisciplinary approach to ERT, emphasizing indications, contraindications, procedural techniques, and team coordination to optimize outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, integrating anatomical, physiological, and operational considerations. The review synthesizes evidence on patient selection, procedural steps, equipment requirements, and interprofessional roles, alongside complication profiles and survival data. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> ERT demonstrates its greatest benefit in penetrating thoracic injuries with reversible causes of arrest, such as tamponade or exsanguination. Survival rates remain low (7.4–8.5%), but meaningful salvage is possible when strict criteria are met. Contraindications include prolonged pulselessness (>15 minutes), absence of signs of life, and unsurvivable injuries. Key procedural elements include rapid thoracic entry, hemorrhage control, pericardial decompression, and aortic cross-clamping. Success depends on system readiness, simulation-based training, and seamless team coordination. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> ERT is a last-resort intervention that can convert imminent death into survival when applied judiciously. Its effectiveness hinges on rigorous patient selection, technical proficiency, and integrated trauma systems.